Peripheral Glial Cells in the Development of Diabetic Neuropathy - Gonçalves, Nádia Pereira; Vægter, Christian Bjerggaard; Pallesen, Lone Tjener (Frontiers in Neurology, 2018)
The global prevalence of diabetes is rapidly increasing, affecting more than half a billion individuals within the next few years. As diabetes negatively affects several physiological systems, this dramatic increase represents not only impaired quality of life on the individual level but also a huge socioeconomic challenge. One of the physiological consequences affecting up to half of diabetic patients is the progressive deterioration of the peripheral nervous system, resulting in spontaneous pain and eventually loss of sensory function, motor weakness and organ dysfunctions. Despite intense research on the consequences of hyperglycemia on nerve functions, the biological mechanisms underlying diabetic neuropathy are still largely unknown, and treatment options lacking. Research has mainly focused directly on the neuronal component, presumably from the perspective that this is the functional signal-transmitting unit of the nerve. However, it is noteworthy that each single peripheral sensory neuron is intimately associated with numerous glial cells; the neuronal soma is completely enclosed by satellite glial cells and the length of the longest axons covered by at least 1,000 Schwann cells. The glial cells are vital for the neuron, but very little is still known about these cells in general and especially how they respond to diabetes in terms of altered neuronal support. We will discuss current knowledge of peripheral glial cells and argue that increased research in these cells is imperative for a better understanding of the mechanisms underlying diabetic neuropathy.